2016
DOI: 10.1111/cas.12941
|View full text |Cite
|
Sign up to set email alerts
|

Gene aberrations for precision medicine against lung adenocarcinoma

Abstract: Lung adenocarcinoma (LADC), the most frequent histological type of lung cancer, is often triggered by an aberration in a driver oncogene in tumor cells. Examples of such aberrations are EGFR mutation and ALK fusion. Lung adenocarcinoma harboring such mutations can be treated with anticancer drugs that target the aberrant gene products. Additional oncogene aberrations, including RET,ROS1, and NRG1 fusions, skipping of exon 14 of MET, and mutations in BRAF,HER2,NF1, and MEK1, were recently added to the list of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
132
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 72 publications
(121 reference statements)
9
132
0
1
Order By: Relevance
“…Lung cancer is the most common malignancy and the leading cause of cancer-related deaths worldwide (1) whereas lung adenocarcinoma is the most frequent histological subtype of lung cancer (2). Oncogene aberrations have been extensively studied in the adenocarcinoma subtype (3), and show great molecular heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the most common malignancy and the leading cause of cancer-related deaths worldwide (1) whereas lung adenocarcinoma is the most frequent histological subtype of lung cancer (2). Oncogene aberrations have been extensively studied in the adenocarcinoma subtype (3), and show great molecular heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been dramatic advances in the treatment of lung adenocarcinoma because of the development of therapies targeting driver oncogene alterations, for example, drugs targeting the epidermal growth factor receptor (EGFR) mutation or the anaplastic lymphoma kinase (ALK) fusion [1, 2]. However, most patients will inevitably develop acquired resistance to the targeted therapy [35].…”
Section: Introductionmentioning
confidence: 99%
“…A multistage GWAS (genome‐wide association studies) on lung cancer suggested that lung tumors attributed to differing carcinogens may have developed from individual genetic risk markers . And most notably, lung adenocarcinoma (LADC), the most frequent histological type of lung cancer, has exploited and elevated the clinical application of effective molecular targeted therapies . The effectiveness of precision medicine against LADCs urgently requires peculiar molecular markers and novel therapeutic strategies from vast changes in gene regulation.…”
Section: Introductionmentioning
confidence: 99%